Droughts in Finland - past, present and future - Kuusisto, Esko, author; Colorado State University, publisher (Colorado State University. Libraries, 2004)
A drought hit most of Norway, Sweden and Finland in 2002-03 with a considerable reduction in hydropower production – and a considerable increase in the price of electricity. In Sweden the second half of 2002 was one of the driest in hundred years, in southern Finland the precipitation in August 2002 – April 200l was less than half of the average. In general, droughts are neither frequent nor severe in northern Europe, but they do occur. In Finland the most serious 20th century drought occurred in 1940-42. Mean annual countrywide discharge was only 49% of long-term average in 1941 and 47% in 1942. These were the tow driest years in the whole 20th century. Some knowledge on droughts before the instrumental period can be inferred from tree ring-widths. Prolonged sequences of sever summer droughts took place in southern Finland in 933-945, 1173-1191, 1988-1402 and 1664-1680. Some indications of cycles corresponding to periods of approximately 23, 30 and 57 years have been detected. In the present climate, the ratio of winter low flows to summer low flows is less than 0.5 in northern Finland, but over 2.0 in southwestern parts of the country. Climate change may alter these values significantly. Increasing trends of winter flows have already been observed in southern and central Finland.
Hydrology days 2004
AGU hydrology days 2004
24th annual AGU hydrology days was held at Colorado State University on March 10-12, 2004.